Advanced chronic total occlusion–percutaneous coronary intervention techniques in managing complex in-stent restenosis - Gautam Swaroop (Heart India)
Chronic total occlusions (CTOs) with in-stent restenosis (ISR) pose significant challenges in interventional cardiology. This case report describes the successful revascularization of a 58-year-old male with an ISR-related CTO of the right coronary artery. After the antegrade approach failed, a retrograde strategy via septal collaterals was employed. Key techniques included retrograde wire crossing, microcatheter support, and intravascular ultrasound-guided stent optimization. Despite severe calcification and bifurcation involvement, strategic planning and hybrid percutaneous coronary intervention (PCI) techniques ensured optimal revascularization. This case highlights the importance of advanced CTO-PCI strategies in managing complex coronary occlusions.